INTERAKSI ANTARBUDAYA MASYARAKAT SUKU MELAYU DAN SUKU BATAK DI KECAMATAN BATU AJI - Aisyiah Indah Permata; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
Intercultural interaction between the Malay and Batak communities in Batuaji Sub-district runs harmoniously despite cultural differences. Challenges such as differences in language and customs still exist, but efforts to improve intercultural communication continue. The purpose of this study was to determine the intercultural interaction of the Malay tribe and the Batak tribe in Batuaji sub-district. The research method used a descriptive qualitative approach, focusing on the intercultural interactions of the two tribes. The results showed that in Batu Aji sub-district, there is a domination by the Batak community both in terms of population, habits, and culture compared to the Malay tribe. Batak people tend to actively participate in activities, like to gather with extended family, and have a very firm mindset and attitude. In contrast, from the perspective of the Batak people, they see that the Malays rarely contribute to neighborhood activities, speak with a fast tone and unclear intonation, making it difficult to understand. Despite these differences, individuals from these two tribes can still establish a good relationship in social life. It can be seen that the dominance of Batak culture affects the mixed family life between Batak and Malay tribes. The use of Batak language in conversation, especially when angry or upset, as well as the assertive attitude and result-focused way of thinking, creates a certain dynamic in the family.